UPACARA KEMATIAN SAURMATUA PADA ADAT MASYARAKAT BATAK TOBA( STUDI KASUS TENTANG KESIAPAN KELUARGA ) DI DESA PURBATUA KECAMATAN PURBATUA KABUPATEN TAPANULI UTARA - Junita S, Eva; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Death is the end of the journey of human life. So death is basically a matter of course, that should not be feared, because sooner or later it will pick up the life of each human being. However, only natural that death is not the main desire of man. Various human effort will always be taken to avoid death, at least slow death came. Ideally death came at a very old age, such as the death of Saur Matua.Saur Matua is the one who died superbly well to have children and grandchildren of the boys and of girls. Saur means complete or perfect where it is said that those who had died had been perfect in kinship, have had children and have grandchildren. So if the deceased perfect in kinship then customary burial ceremony was held perfectly (Saur matua). If it had been a perfect death, then it must be made perfectly pemberangkatannya event, called ulaon na gok (event with full custom). Ulaon na gok implemented maralaman (on the home page). Boan (food) prepared is sigagat duhut (buffalo). In the ceremony Saur matua all the family, siblings, parents, young people and all citizens no matter where he is, like; on the shoreline, fields, settlements in the farm that is located far from villages or other settlements. They are present, unite, come together to deliver the final resting place of the bodies.Keywords: Culture and Society Batak Toba Batak Toba